Stealth Non-standard-model Confined Flare Eruptions: Sudden Reconnection Events in Ostensibly Inert Magnetic Arches from Sunspots - Ronald L. Moore; Sanjiv K. Tiwari; Navdeep K. Panesar; V. Aparna; Alphonse C. Sterling (The Astrophysical Journal, 2024)
We report seven examples of a long-ignored type of confined solar flare eruption that does not fit the standard model for confined flare eruptions. Because they are confined eruptions, do not fit the standard model, and unexpectedly erupt in ostensibly inert magnetic arches, we have named them stealth non-standard-model confined flare eruptions. Each of our flaring magnetic arches stems from a big sunspot. We tracked each eruption in full-cadence UV and EUV images from the Atmospheric Imaging Assembly of Solar Dynamics Observatory (SDO) in combination with magnetograms from SDO’s Helioseismic and Magnetic Imager. We present the onset and evolution of two eruptions in detail: one of six that each makes two side-by-side main flare loops, and one that makes two crossed main flare loops. For these two cases, we present cartoons of the proposed pre-eruption field configuration and how sudden reconnection makes the flare ribbons and flare loops. Each of the seven eruptions is consistent with being made by sudden reconnection at an interface between two internal field strands of the magnetic arch, where they cross at a small (10°–20°) angle. These stealth non-standard-model confined flare eruptions therefore plausibly support the idea of E. N. Parker for coronal heating in solar coronal magnetic loops by nanoflare bursts of reconnection at interfaces of internal field strands that cross at angles of 10°–20°.